A 5′-to-3′ strand exchange polarity is intrinsic to RecA nucleoprotein filaments in the absence of ATP hydrolysis. Issue 10 (27th March 2019) - Lin, Yu-Hsuan; Chu, Chia-Chieh; Fan, Hsiu-Fang; Wang, Pang-Yen; Cox, Michael M; Li, Hung-Wen
Abstract: RecA is essential to recombinational DNA repair in which RecA filaments mediate the homologous DNA pairing and strand exchange. Both RecA filament assembly and the subsequent DNA strand exchange are directional. Here, we demonstrate that the polarity of DNA strand exchange is embedded within RecA filaments even in the absence of ATP hydrolysis, at least over short DNA segments. Using single-molecule tethered particle motion, we show that successful strand exchange in the presence of ATP proceeds with a 5′-to-3′ polarity, as demonstrated previously. RecA filaments prepared with ATPγS also exhibit a 5′-to-3′ progress of strand exchange, suggesting that the polarity is not determined by RecA disassembly and/or ATP hydrolysis. RecAΔC17 mutants, lacking a C-terminal autoregulatory flap, also promote strand exchange in a 5′-to-3′ polarity in ATPγS, a polarity that is largely lost with this RecA variant when ATP is hydrolyzed. We propose that there is an inherent strand exchange polarity mediated by the structure of the RecA filament groove, associated by conformation changes propagated in a polar manner as DNA is progressively exchanged. ATP hydrolysis is coupled to polar strand exchange over longer distances, and its contribution to the polarity requires an intact RecA C-terminus.